2022
DOI: 10.7759/cureus.26555
|View full text |Cite
|
Sign up to set email alerts
|

Incidental and Asymptomatic Splenic Infarction and Infrarenal Thrombus in a COVID-19 Patient

Abstract: The cytokine storm associated with coronavirus disease 2019 (COVID-19) triggers a hypercoagulable state leading to venous and arterial thromboembolism. Lab findings associated with this phenomenon are elevated D-dimer, fibrinogen, C-reactive protein (CRP), ferritin, and procalcitonin. We present the case of a 66-year-old male with dyslipidemia who was diagnosed with COVID-19 with worsening shortness of breath, myalgia, and loss of taste. Physical examination was remarkable for crackles with diminished lung sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…For non-critically ill patients hospitalized with COVID-19, a high index of suspicion is necessary for detecting thromboembolism, especially when the patient presents with acute abdominal pain, chest pain, or lower extremity pain [ 17 , 18 ]. Therapeutic-dose heparin appears beneficial, with a high probability of reducing the need for organ support and the progression to intubation and death, regardless of D-dimer results [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…For non-critically ill patients hospitalized with COVID-19, a high index of suspicion is necessary for detecting thromboembolism, especially when the patient presents with acute abdominal pain, chest pain, or lower extremity pain [ 17 , 18 ]. Therapeutic-dose heparin appears beneficial, with a high probability of reducing the need for organ support and the progression to intubation and death, regardless of D-dimer results [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…10 Symptomatic arterial thrombosis is diagnosed clinically combined with imaging of CTA, which is preferable, while asymptomatic and atypical splenic infarction was discovered incidentally on CTA. 11 The causes of SI include atherosclerotic embolus, hypercoagulation-related diseases such as cancer, arterial damage, abnormal clotting factors, and inflammation. In a retrospective study of patients with SI, Wand et al suggested that SI could be the initial presentation of previously unknown medical conditions in 38% of patients.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Symptomatic arterial thrombosis is diagnosed clinically combined with imaging of CTA, which is preferable, while asymptomatic and atypical splenic infarction was discovered incidentally on CTA. 11 …”
Section: Discussionmentioning
confidence: 99%
“…Splenic and renal infarction are rare ischemic abdominal complications in COVID-19 patients and have only been presented in case reports and a few case series [ 147 , 149 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 ]. Splenic and renal infarctions generally have a minor clinical impact compared to intestinal infarction.…”
Section: Vascular Abdominal Extrapulmonary Complicationsmentioning
confidence: 99%